TRANSFORMASI LAHAN PEKARANGAN SEBAGAI BASIS EKONOMI MASYARAKAT: ANALISIS TEORI JIM IFE - Amalia Nurusifa sari (LPPM STAI Muhammadiyah Probolinggo, 2025)
This study aims to examine how the transformation of yard land into a community economic base can be realized through the lens of Jim Ife's empowerment theory with a local power approach, active community participation, and dimensions of social and ecological sustainability. With a qualitative approach and case studies, involving field observations, interviews and documentation. The core problem in this study is the suboptimal utilization of yard land as an economic resource in Blederan Village due to misperceptions about the function of yards, dependence on chemical farming, and the high percentage of landless households (76%). This causes the potential for saving Rp3,000/day per household on vegetables and increasing food security to not be fully utilized, so that an empowerment approach based on local potential through education and mentoring is needed to transform yards into productive assets that encourage community economic independence. The analysis uses Jim Ife's local power empowerment theory which shows the optimization of local strengths such as traditional wisdom, local natural resources, and social networks. The findings show an increase in household income, food security, and the development of collective social initiatives that are adaptive to ecological challenges. This transformation also strengthens environmental awareness and community solidarity, so that this empowerment model has the potential to become a sustainable strategy that synergistically integrates economic, social, and ecological aspects.